Rheumatic Diseases Presenting with Guillain-Barré Syndrome: Sjögren’s Syndrome and Systemic Lupus Erythematosus - Ebru Aytekin; Hüdanur Coşkun; Yasemin Pekin Doğan; Burak Tayyip Dede; Özer Burnaz; Ufuk Emre (İstanbul Medical Journal, 2020)

(untitled)
The coexistence of Guillain-Barré syndrome (GBS) with autoimmune rheumatic diseases is extremely rare. In addition to flu, infection, trauma, vaccination, blood transfusion, chemotherapy and surgical intervention, rheumatic diseases may be the underlying etiological cause of resistant and prolonged GBS cases. Therefore, appropriate treatments specific to rheumatic diseases may accelerate the healing process, reduce the possibility of neurological sequelae and greatly contribute to the rehabilitation process.